The impact of aging and drag-finishing on the surface integrity and corrosion behavior of the selective laser melted maraging steel samples - KAYNAK, YUSUF (WILEY-V C H VERLAG GMBH, 2021)
The maraging steel components fabricated using the selective laser melting process exhibit remarkable static strength. However, high pore density and large surface imperfections impede their overall mechanical and chemical performance. Thus, the components are often post-treated with mechanical- and thermal-based treatments to overcome their inherent imperfections and enhance their final mechanical properties. Although the post-processing treatments are useful in enhancing the selective laser melted components' mechanical performance, their effect on corrosion behavior is not comprehensively evaluated. In this study, the selective laser melting prepared maraging steel samples' corrosion behavior was examined in the as-built condition and compared with the post-processed samples subjected to aging and drag finishing operations. Compared to the as-built condition, both aging and drag-finishing post-processing treatments increased the selective laser melting samples' corrosion even though the surface integrity was improved.
Keywords: Corrosion resistance; drag-finishing; heat-treatment; selective laser melting; additive manufacturing; maraging steel